IDENTIFIKASI RISIKO PRODUKSI ROTI PADA INDUSTRI RUMAHAN ORCHARD BAKERY DI KABUPATEN PURWAKARTA - Budiyono, Haris; Ardisela, Dawud; Prakoso, Nasha Bagas (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
The production process in baking industry should be carefully managed, by identifying and handling the major of risks that could lead to failures of final products. This study was conducted to identify the major of risks on production process in The Orchard Bakery, located in Purwakarta Regency, West Java. Failure Mode and Effect Analysis (FMEA) and pareto diagram were used to examine the major sources of risk that would impact on the quality of bread produced. Failure Mode and Effects Analysis (FMEA) is a method that systematically done to identify potential problems, or failures and their resulting effects on production process. In this method, Risk Priority Numbers (RPN) were measured and calculated based on past experiences and judgements to rate each potential problems, by rating 3 (three) aspects on the risks: severity, occurrence, and detection. The results of this study find 6 (six) sources of risk with high RPN values, as a pareto chart indicates that their cumulative impacts totalled 80%, namely: packaging (19%), dough making (16%), baking (16%), proofing (13%), handling quality of final products (9%), and selection of main and supporting ingredients (7%).